Raltegravir Attenuates Experimental Pulmonary Fibrosis In Vitro and In Vivo - Zhang, Xue; Huang, Haidi; Zhang, Guanghua; Li, Defang; Wang, Hongbo; Jiang, Wanglin (Frontiers in Pharmacology, 2019)
Raltegravir, an inhibitor of the human immunodeficiency virus-1 (HIV-1) integrase, is used to treat HIV/acquired immunodeficiency syndrome; however, its therapeutic effects on pulmonary fibrosis have not been investigated. In this study, the effects of raltegravir on transforming growth factor beta 1-induced pulmonary fibrosis in vitro in L929 mouse fibroblasts were investigated. In addition, the effects of raltegravir on an in vivo pulmonary fibrosis model induced by intratracheal instillation of bleomycin were investigated. The proliferation of L929 cells was inhibited after raltegravir treatment. Meanwhile the protein expression of nucleotide-binding oligomerization domain-like receptor 3 (NLRP3), high mobility group box 1 (HMGB1), toll-like receptor 4 (TLR4), prolyl hydroxylase domain protein 2, phosphorylated nuclear factor-κB (p-NF-κB), hypoxia-inducible factor-1α (HIF-1α), collagen I, and collagen III was reduced relative to the model group both in vitro and in vivo. Raltegravir ameliorated pulmonary fibrosis by reducing the pathology score, collagen deposition, and expression of α-smooth muscle actin, NLRP3, HMGB1, TLR4, inhibitor of kappa B, p-NF-κB, HIF-1α, collagen I, and collagen III. The results of this study demonstrated that raltegravir attenuated experimental pulmonary fibrosis by inhibition of NLRP3 activation.